Archaeometallurgical experimentation on technical ceramics from pre-hispanic Northwestern Argentina - Gluzman, Geraldine Andrea (2025)
We present the progress of an experimental archaeology program focused on the production methods of technical ceramics for bronze and copper manufacturing in pre-Hispanic Northwestern Argentina. Our experimental procedure involved two phases: the fabrication of twenty briquettes with cavities (molds) and the casting of molten copper into these cavities. Our experimental design was based on the technological and functional characteristics of archaeological samples from the region. The briquettes were made using clays and non-plastic materials from the Yocavil Valley (Catamarca, Argentina) and then fired. Different proportions of clay and temper were tested, and firing conditions, shrinkage rates, and porosity levels were evaluated. The final phase consisted of a copper casting to evaluate the performance of each briquette as a small mold, analyzing how each one responded when the metal was poured. This work is part of an experimental archaeology approach aimed at gaining deeper insight into the technological knowledge applied in the production of specialized ceramics used in metallurgical contexts. By reconstructing some of the variables of manufacture in a controlled setting, we offer new perspectives on the material knowledge and practices that sustained metal production in pre-Hispanic societies of the Southern Andes.